2020
DOI: 10.3390/nu12061838
|View full text |Cite
|
Sign up to set email alerts
|

Nutrihealth Study: Seasonal Variation in Vitamin D Status Among the Slovenian Adult and Elderly Population

Abstract: Several studies conducted around the world showed substantial vitamin D insufficiency and deficiency among different population groups. Sources of vitamin D in the human body include ultraviolet B (UVB)-light-induced biosynthesis and dietary intake, but people’s diets are often poor in vitamin D. Furthermore, in many regions, sun exposure and the intensity of UVB irradiation during wintertime are not sufficient for vitamin D biosynthesis. In Slovenia, epidemiological data about vitamin D status in the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(68 citation statements)
references
References 56 publications
4
63
1
Order By: Relevance
“…<20 ng/ml or <50 nmol/l). 25,27,31,34,[39][40][41]43,[45][46][47] The size of study population which was used to retrieve data for the prevalence of Vit D deficiency varied from 280 (Slovenia) 43 to 74.235 subjects (Italy). 37 As of February, 4 th We also examined the relationships between COVID-19 infections, recoveries and deaths with the mean vitamin D concentration of each country, as can been seen in the Supplementary Material, but again no significant correlation was found.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…<20 ng/ml or <50 nmol/l). 25,27,31,34,[39][40][41]43,[45][46][47] The size of study population which was used to retrieve data for the prevalence of Vit D deficiency varied from 280 (Slovenia) 43 to 74.235 subjects (Italy). 37 As of February, 4 th We also examined the relationships between COVID-19 infections, recoveries and deaths with the mean vitamin D concentration of each country, as can been seen in the Supplementary Material, but again no significant correlation was found.…”
Section: Resultsmentioning
confidence: 99%
“…<20 ng/ml or <50 nmol/l). 25,27,31,34,39-41,43,45-47 The size of study population which was used to retrieve data for the prevalence of Vit D deficiency varied from 280 (Slovenia) 43 to 74.235 subjects (Italy). 37…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, substantial proportions of the European population rely on dietary vitamin D and body stores to maintain a sufficient vitamin D status during the extended winter season, and quite a high prevalence of vitamin D deficiency is reported in many countries worldwide (30)(31)(32)(33). Alarmingly, in a very recent nationally representative study for Slovenia (34), during the extended winter season vitamin D deficiency was found in about 80% of adults (18-74 years), while almost 40% had a severe vitamin D deficiency, with serum 25(OH)D levels below 30 nmol/l.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant example involves food supplements intended for supplementing vitamin D. In many countries, an extremely high prevalence of vitamin D deficiency has been reported, particularly during winter periods [34][35][36], due to seasonal variations in the efficiency of the ultraviolet B (UVB)-induced biosynthesis of vitamin D in human skin [37]. In Slovenia, for example, about 80% of the adult population was found to have insufficient vitamin D levels between October and April [35]. Though there are differences between countries, the recommended daily intake of vitamin D for adults (in the absence of endogenous synthesis) is usually between 15 and 20 µg [38,39].…”
Section: Introductionmentioning
confidence: 99%